Sosialisasi Gerakan Menanam 1 Juta Pohon Matoa di Indonesia: Socialization of the Movement to Plant 1 Million Matoa Trees in Indonesia - Fitria, Fanny; Fitriani, Fitriani; Fikra, Hidayatul; Darmalaksana, Wahyudin (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to conduct literacy on the Matoa tree planting movement policy throughout Indonesia for the purpose of socialization. This study uses a qualitative approach by implementing a policy literacy study. The results of the study and discussion show that the policy on the Matoa tree planting movement is an implementation of an ecotheological program that integrates religious values ​​and environmental conservation. This policy is a model for environmental sustainability efforts based on religious participation by contributing to maintaining ecosystem balance and mitigating climate change. This study concludes that the tree planting movement is understood as a manifestation of moral and spiritual responsibility in maintaining the ecosystem sustainably as a National movement that brings long-term benefits to future generations in Indonesia.